Temperature Dependent on Mechanical and Rheological Properties of EPDM-Based Magnetorheological Elastomers Using Silica Nanoparticles - Rashid, R.Z.A. (MDPI, 2022)
Temperature is one of the most influential factors affecting the performance of elastomer matrix in magnetorheological elastomer (MRE). Previous studies have utilized silica as a reinforcing filler in polymer composite and as a coating material in MRE to improve the thermal stability of the base material. However, the usage of silica as an additive in the thermal stability of MRE has not been explored. Thus, in this study, the effect of silica as an additive on the temperature-dependent mechanical and rheological properties of ethylene propylene diene monomer (EPDM)-based MREs was investigated by using 30 wt. carbonyl iron particles (CIPs) as the main filler, with different contents of silica nanoparticles (0 to 11 wt.). The microstructure analysis was examined by using field-emission scanning electron microscopy (FESEM), while the thermal characterizations were studied by using a thermogravimetric analyzer and differential scanning calorimetry. The tensile properties were conducted by using Instron Universal Testing Machine in the absence of magnetic field at various temperatures. Meanwhile, the rheological properties were analyzed under oscillatory loadings in the influence of magnetic field, using a rotational rheometer at 25 to 65â¦ C. The results revealed that the temperature has diminished the interfacial interactions between filler and matrix, thus affecting the properties of MRE, where the tensile properties and MR effect decrease with increasing temperature. However, the presence of silica capable improved the thermal stability of EPDM-based MRE by enhancing the interactions between filler and matrix, thus reducing the interfacial defects when under the influence of temperature. Consequently, the incorporation of silica nanoparticles as an additive in EPDM-based MRE requires more exploration, since it has the potential to sustain the properties of MRE devices in a variety of temperature conditions. Thus, the study on the temperature-dependent mechanical and rheological properties of MRE is necessary, particularly regarding its practical applications. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.